Global economy: Recovery slowing down - Claus Michelsen; Paul Berenberg-Gossler; Geraldine Dany-Knedlik; Hella Engerer; Sandra Pasch (DIW Weekly Report, 2020)
The global economy recovered more quickly than expected in the third quarter of 2020. Following the coronavirus-related slumps, economic output increased by seven percent. A decrease in infection rates and thus an easing of containment measures contributed to re-normalizing production processes and trade. Private households also began demanding more consumer goods again, especially personal services. However, the second wave in fall 2020 will slow down the recovery. In 2020, global production will shrink by 3.4 percent; the growth rates in 2021 and 2022, 6.3 and 4.4 percent respectively, are likely to be stronger than forecasts in fall 2020. Despite this, there are many risks: Even though the vaccine breakthroughs are promising, other uncontrolled increases in coronavirus cases could occur. Furthermore, the extent to which corporate insolvencies will increase and how a wave of insolvencies would impact economic recovery cannot be predicted.
Keywords: E32; E66; F01; 330; Business cycle forecast; ecoomic outlook